2023
DOI: 10.1021/acs.jpcb.3c02947
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport in Poly(p-phenylene): Anomalous Dimensionality Dependence and Role of π–π Stacking

Abstract: For heat conduction along polymer chains, a decrease in the axial thermal conductivity often occurs when the polymer structure changes from onedimensional (1D) to three-dimensional (3D). For example, a single extended aliphatic chain (e.g., polyethylene or poly(dimethylsiloxane)) usually has a higher axial thermal conductivity than its double-chain or crystal counterparts because coupling between chains induces strong interchain anharmonic scatterings. Intuitively, for chains with an aromatic backbone, the eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Fundamentally, this finding also challenges the current understanding on thermal transport in 2D HOIPs that appear to coherently transport heat across the organic–organic interface. , The unusual correlation between thermal conductivity and elastic modulus highlights the importance of optical phonons in regulating room temperature heat flow in 2D HOIPs depending on the interface type. , Optical phonons may not necessarily contribute to thermal conductivity, but rather provide strong scattering channels for acoustic phonons, as claimed for all-inorganic 2D HOIPs . Another possibility is the large mismatch of phonon spectrum at the aryl–aryl and alkyl–aryl interfaces induces a strong phonon filtering effect . Indeed, studies on thermal transport in 2D HOIPs have only recently begun to emerge and would require further investigations.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Fundamentally, this finding also challenges the current understanding on thermal transport in 2D HOIPs that appear to coherently transport heat across the organic–organic interface. , The unusual correlation between thermal conductivity and elastic modulus highlights the importance of optical phonons in regulating room temperature heat flow in 2D HOIPs depending on the interface type. , Optical phonons may not necessarily contribute to thermal conductivity, but rather provide strong scattering channels for acoustic phonons, as claimed for all-inorganic 2D HOIPs . Another possibility is the large mismatch of phonon spectrum at the aryl–aryl and alkyl–aryl interfaces induces a strong phonon filtering effect . Indeed, studies on thermal transport in 2D HOIPs have only recently begun to emerge and would require further investigations.…”
Section: Resultsmentioning
confidence: 92%
“…This comparison seems to indicate that the rings are more closely packed (smaller spacing) in full-chiral 2D HOIPs than the aryl–alkyl and aryl–aryl spacings in half-chiral 2D HOIPs. This is also indicative of the importance of orientation of the rings in determining thermal transport across aryl–aryl type interface . A notable difference between the structures of [SMePEA] 2 PbI 4 and [PEA] 2 PbI 4 is the presence of several diverse orientations of rings in the former.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12(b)). Conversely, the relation between thermal conductivity and dimensionality can be inverted if the chains are bonded and aligned in the perpendicular plane to the chain length, as demonstrated by Yang et al 233 in their study of aromatic poly( p -phenylene). They showed that the 3-D crystalline form exhibits greater thermal conductivity compared to both double-chain (2-D) and single-chain (1-D) configurations, as depicted in Fig.…”
Section: Molecular Scale Effects For Thermal Transport In Polymersmentioning
confidence: 99%
“…(c) Thermal conductivity for single-chain, double-chain, and crystal as a function of a number of segments of poly(pphenylene). Reproduced with permission 233. Copyright, 2023, American Chemical Society -JPCB.…”
mentioning
confidence: 99%